Kebijakan Hukum Pidana Dalam Upaya Penanggulangan Tindak Pidana Korupsi Sebagai Kontribusi Pembaharuan Hukum Pidana - Ghaffar Rabbani; Fudail Syabil (Universitas Sains dan Teknologi Komputer, 2023)
Pregnant women experiencing Chronic Energy Deficiency (CED) usually have occurred for a long time, and this is a condition that should be avoided during pregnancy, because one of the effects is that the growth and development of the fetus is hampered. In Surakarta City itself there are still pregnant women in SEZ conditions, so the government has responsibilities, one of which is through handling Supplemental Feeding (PMT). The condition of KEK pregnant women getting additional PMT in Surakarta City has not all been fulfilled, it was recorded that in 2021 it reached 94.43%, which shows that there are still KEK pregnant women who have not received PMT. Judging from the handling every year, in the last two years it has continued to increase, meaning that it has improved.